Perlindungan Hukum Terhadap Konsumen Dalam Permberian Permen Sebagai Alternatif Uang Kembalian - Syukran Haberlin; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2026)
The practice of giving candy as a substitute for monetary change by business actors is an act that contradicts the principles of consumer protection as stipulated in Law Number 8 of 1999 concerning Consumer Protection (UUPK). This practice violates consumer rights as outlined in Article 4 of the UUPK, particularly the rights to comfort, safety, accurate information, fair and non-discriminatory treatment and Law Number 7 of 2011 concerning Currency. This research aims to examine the legal protection available to consumers subjected to this practice and to describe the legal responsibilities of business actors under the prevailing laws and regulations. The study uses a normative legal method with a statutory approach. The findings show that legal protection for consumers in such cases can be pursued through two approaches: preventive (education and regulation) and repressive (complaints to the Consumer Dispute Settlement Agency [BPSK], Indonesian Consumers Foundation [YLKI], or through civil/criminal lawsuits). The responsibility of business actors extends beyond business ethics and includes civil, administrative, and even criminal liability. If the act causes actual harm to the consumer, the business actor is obligated to provide compensation as stipulated in Article 19 of the UUPK and may be subject to criminal sanctions under Article 62 of the UUPK. Furthermore, the act may fulfill the elements of fraud as defined in Article 378 of the Indonesian Criminal Code (KUHP). Therefore, collaboration among the government, business actors, and society is essential to create a consumer protection system that is fair, transparent, and upholds legal justice.